If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 6 = 3x Combine like terms: 17 + 6 = 23 23 = 3x Solving 23 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 23 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 23 + -3x = 0 Add '-23' to each side of the equation. 23 + -23 + -3x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 0 + -23 -3x = 0 + -23 Combine like terms: 0 + -23 = -23 -3x = -23 Divide each side by '-3'. x = 7.666666667 Simplifying x = 7.666666667
| -4x+10=-3(2x+2) | | 660/x=25/3 | | 0.4(x-4)=4.0 | | (x-3+9i)(x-3-9i)=0 | | 3y+8x=12 | | X*.03=28 | | 1/5(3x-4)=2/5 | | 1-x+4x+17=3x | | h([-3])=2x+4 | | y=0+(-4) | | 6x^2+12x=4 | | 4=-y | | 2x+6=8x-31 | | .85=200 | | 3x-12+15=2x+10 | | 5y-9+y+36=8y+30-5y | | 0.8=200 | | 13x+7=5x+7 | | 4(lnx)-lnx^4=0 | | 7x+8=7x+3 | | 0.25=10 | | 5x+3=-3+3x+22 | | x+7x+4+2x=30+4 | | 2x-17=11-5x | | x+x=x+222 | | 5a^2-5a+1=0 | | (3x+2z)(2x-7z)= | | 33-3x=12x | | y=6(x-1)+9 | | 9x+4=12x+6 | | 3x(x+4)=18 | | 4x-12+16=3x+12 |